ANALISIS PENGURANGAN KUANTITAS PRODUK CACAT PADA MESIN DECORATIVE TILES DENGAN METODE SIX SIGMA (Studi Kasus Pada PT Aster Decorindo Abadi Tangerang) - Muttaqien, Achmad Faizal; Rahardjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2014)
The continued development of technology in today's age of globalization makes trade easier. From these circumstances lead to increasingly tight competition in the market.from these competition company makes to required to maintain the product quality to meet customer needs. To fill the ever-increasing needs of consumers, the company must determine the quality factor demanded by consumers beside from price, design or other.PT. Aster Decorindo Abadi is a company which operate in decorative tiles or ceramic design with the different types. In the production activity, the company is always trying to produce a good product and reduce high product defects to by setting a standards with 7% of total production. However, in the reality, defect levels fluctuate and sometimes exceeds the specified tolerance standards.Six Sigma is a quality target with a value is 3.4 DPMO (Defect per Million Oppurtunity) or 3.4 defects per million opportunities of. The existence of the achievement of six sigma is 3.4 DPMO it can be to achieve the reality of quality based on zero defect. Reduction on quantity of disability research using six sigma DMAIC with discussion (Define, Measure, Analyze, Improve, Control). The aim of this study was to determine the achievement of sales targets without knowing the product is defective and flawed because it occurs by using the six sigma method.From the analysis result and research that has been done turns out the number of product defects in PT. Aster Decorindo Abadi in the 3.23 sigma level with DPMO values of 40 348. From that way it can be identified that the product quality was still far from the level of 6 sigma products (conversion). With using of a cause and effect diagram analysis can be known the factor cause of damage or defects to the product in production it comes from humans, machines, raw materials and work environment.